Improving Rope Jumping Abilities Using The Demonstration Method In Grade IV Students of SD Inpres 1 Besusu (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to improve the rope jumping ability of fourth grade students of SD Inpres 1 Besusu through the application of the demonstration method. The study used a Classroom Action Research (CAR) approach which was implemented in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 17 students, consisting of 8 male students and 9 female students. The research instruments were observation sheets and rope jumping skills tests. The results showed an increase in rope jumping ability in each cycle. In the pre-cycle, only 11.76% of students reached the good category, while 64.70% were in the poor category. After the action was carried out in the first cycle, the number of students in the good category increased to 17.64%, the sufficient category to 47.05%, and the poor category decreased to 35.29%. In the second cycle, a significant increase was seen with 76.47% of students in the good category, 17.64% in the sufficient category, and only 5.88% in the poor category. The research success indicator, namely a minimum of 75% of students achieving the good category, was achieved in cycle II. These results demonstrate that the demonstration method is effective in improving students' basic motor skills, particularly in rope jumping. The study recommends that physical education teachers utilize the demonstration method more effectively in teaching basic motor skills